Influence of Depressive Symptoms on Dopaminergic Treatment of Parkinson’s Disease - Hanganu, Alexandru; Degroot, Clotilde; Monchi, Oury; Bedetti, Christophe; Mejia-Constain, Béatriz; Lafontaine, Anne-Louise; Chouinard, Sylvain; Bruneau, Marie-Andrée (Frontiers in Neurology, 2014)
Introduction: Depressive symptoms are very common in patients with Parkinson’s disease and have a significant impact on the quality of life. Dopaminergic medication has been shown to have an influence on the development of depressive symptoms. Material and Methods: The present study analyzed two groups of non-demented patients with Parkinson’s disease, with and without depressive symptoms, and reported the correlations between antiparkinsonian medication (specifically levodopa and dopaminergic agonists) with depressive symptoms. Results: A strong statistically significant positive correlation between levodopa dosages and the level of depressive symptoms has been revealed, suggesting that higher levodopa dosages correlate with a worsening of depressive status. No significant correlation was found with dopamine agonists. Discussion: The results of this study show that in patients with Parkinson’s disease, higher levodopa dosages correlate with worse depressive symptoms. From this point of view, Parkinson’s disease patients need to be better diagnosed with respect to depressive symptoms and need additional treatment adjustment when clinical manifestations of depression are present. Clinicians must be aware that dopaminergic drugs are not sufficient to alleviate depressive symptoms.